The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1136/hrt.2005.078089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of balloon occlusion during percutaneous coronary intervention on circulating Ischemia Modified Albumin and transmyocardial lactate extraction

Abstract: S tudies have shown that human albumin undergoes a considerable reduction in its capacity to bind exogenous cobalt (Ischemia Modified Albumin (IMA); Ischemia Technologies, Denver, Colorado, USA), as measured by the albumin cobalt binding test, when exposed to an ischaemic insult. We have recently observed that plasma IMA levels increase soon after transient balloon inflation during percutaneous coronary intervention (PCI), even in the absence of considerable elevations of cardiac troponin. 1 Higher IMA levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 5 publications
2
45
0
3
Order By: Relevance
“…It was shown that PCI represents a clinical model of myocardial reperfusion characterized by a postoperatory increase in oxidative stress [18]. APO may protect against ischemia-reperfusion myocardial injury by reducing ROS/reactive nitrogen species overproduction by multiple upstream signaling pathways [19], hence the possible intervention of APO in artery protection against ISR lesion.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that PCI represents a clinical model of myocardial reperfusion characterized by a postoperatory increase in oxidative stress [18]. APO may protect against ischemia-reperfusion myocardial injury by reducing ROS/reactive nitrogen species overproduction by multiple upstream signaling pathways [19], hence the possible intervention of APO in artery protection against ISR lesion.…”
Section: Discussionmentioning
confidence: 99%
“…ACB assay has been used in previous studies [35][36][37]. Lee et al [38] developed a cobalt albumin binding assay to correct the flaws of the ACB test with improving the sensitivity and precision.…”
Section: Discussionmentioning
confidence: 99%
“…İskemik dokunun yeniden oksijenlenmesi ile reperfüzyonun ilk 1-5 dakikasında laktat ve ROS oluşumunu izleyen lipid ve protein peroksidasyon ürünleri dolaşıma salınmaktadır. PCI balon şişme sonrası kardiyak troponinler artmamasına rağmen plazma İMA seviyesi artmış olarak tespit edildi (28) . Bar-Or ve arkadaşları yaptığı çalışmada PCI sırasında uyarılan geçici iskemi sonrası ilk 24 saat içinde İMA anlamlı derecede yüksekti ve 6. saatte düşmeye başladığı gösterildi (29) .…”
Section: Akut Mi̇yokart İnfarktüsüunclassified